TOTAL EDGE AND VERTEX IRREGULAR STRENGTH OF TWITTER NETWORK - Rusdi, Edy Saputra; A. Syahrir, Nur Hilal (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
Twitter data can be converted into a graph where users can represent the vertices. Then the edges can be represented as relationships between users. This research focused on determining the total edge irregularity strength (tes) and the total vertices irregularity strength (tvs) of the Twitter network. The value could be determined by finding the greatest lower bound and the smallest upper bound. The lower bound was determined by using the properties, characteristics of the Twitter network graph along with the supporting theorems from previous studies, while the upper bound is determined through the construction of the total irregular labeling function on the Twitter network. The results in this study are the tes(TW)=18 and tvs(TW)=16.